Purchase Decision Drivers in Digital Transactions: The Role of QRIS, Product Quality, and Brand Trust - Asmi, Nurul (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study examines the drivers of purchase decisions in digital healthcare transactions, focusing on the role of QRIS payment convenience, product quality, and brand trust. The rapid adoption of QRIS in Indonesia has improved transaction efficiency, yet evidence suggests that technological ease alone does not guarantee purchase conversion in health-related retail. Understanding how these factors interact is crucial for designing strategies that combine digital convenience with consumer confidence. Background Problems: Despite seamless QRIS adoption at ONEMED Malang, inconsistencies between transaction completion and sustained loyalty persist. This study addresses the research question: How do QRIS convenience, product quality, and brand trust jointly influence consumer purchase decisions in digital healthcare retail? Research Methods: A quantitative explanatory approach was employed using a cross-sectional survey of 460 ONEMED consumers who completed QRIS transactions. Data were collected via structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Finding/Results: The results show that perceived product quality exerts the strongest direct effect on purchase decisions (β = 0.4277), followed by QRIS convenience (β = 0.3306). Both QRIS convenience and product quality significantly influence brand trust, which partially mediates their impact on purchase decisions. The model explains 69.7% of the variance in purchase decisions, indicating high predictive power. Conclusion: Purchase decisions in digital healthcare retail are primarily driven by product quality, supported by QRIS convenience and brand trust. Technological ease alone is insufficient; strategies must integrate quality assurance and trust-building initiatives to achieve sustainable loyalty. ONEMED should combine QRIS adoption with transparent quality signaling and credible communication to strengthen consumer confidence and long-term engagement.